Beyond the Strength of Social Ties: Job Search Networks and Entry-Level Wage in Urban China. (July 2015) - Bian, Yanjie; Huang, Xianbi
This article provides an assessment of the effect of job-search networks on entry-level wage in urban China. The analysis of a 2009 large-scale survey shows that (a) users of social contacts have a significantly higher wage at job entry than nonusers; (b) both strong ties and weak ties increase entry-level wage; (c) network-mobilized information and favoritism increase entry-level wage; and (d) these network effects are stronger in sectors of less institutionalization and for jobs of lower skill specificity, but do not vary significantly from the prereform to the postreform period.